ANALISIS PERILAKU PEKERJA TERHADAP PENERAPAN STANDAR OPERATING PROCEDURE PADA OPERATOR FORKLIFT DI AREA KERJA PRODUKSI COCA-COLA AMATIL INDONESIA CENTRAL JAVA - Chandra Manik; Bina Kurniawan; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Standard Operating Procedure is a form of commitment of Company to apply OSH CCAI Central java has set Standard Operating Procedure, but still many findings of unsafe action conducted by forklift operator in production area. The purpose of this research is to analyze the behavior of forklift operator in applying Standard Operating Procedure in CCAI Central java production area. This research is a qualitative research with the method of observation and in-depth interview. The subjects of this study were 6 people from the forklift production area operator as the main information and 2 person safety officer and the coordinator of the product area forklift operator as the informant triangulation. The research stages are preparation, implementation, data validation and data analysis. The results show that the knowledge about OSH and SOP of the primary informants is sufficient, and the positive response to values and attitudes. Availability of safety sign not yet fully available, availability of SOP / Work Instruction and OSH training. Perceptions of the presence of coordinators of forklift production area operators, safety officers, and colleagues provide a positive influence on the main informant behavior. From this research, it is concluded that the main informant behavior in applying Standard Operating Procedure is still lacking, in practice there are still major informants ignoring aspect of OSH in the form of operating forklift above maximum speed and not wearing APD as according to work done, and availability of safety sign in the production area is not yet 100% fulfilled. The company is expected to immediately complete the safety sign and apply strict sanctions for violators of Standard Operating Procedure.